2012
DOI: 10.1093/hmg/dds474
|View full text |Cite
|
Sign up to set email alerts
|

A novel function for the survival motoneuron protein as a translational regulator

Abstract: SMN1, the causative gene for spinal muscular atrophy (SMA), plays a housekeeping role in the biogenesis of small nuclear RNA ribonucleoproteins. SMN is also present in granular foci along axonal projections of motoneurons, which are the predominant cell type affected in the pathology. These so-called RNA granules mediate the transport of specific mRNAs along neurites and regulate mRNA localization, stability, as well as local translation. Recent work has provided evidence suggesting that SMN may participate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 103 publications
5
105
0
Order By: Relevance
“…Consequently, SMN deficiency may impair targeting and local translation of axonal mRNAs essential for motor neuron development and maintenance 44, 45. Furthermore, SMN regulates several other fundamental cellular processes in the neuronal cytoplasm that are critical for maintaining axonal and synaptic health, including endocytic pathways, local translation, mitochondrial transport, and targeting to axons and ubiquitin homeostasis 46, 47, 48, 49, 50, 51…”
Section: How Low Levels Of Smn Cause Smamentioning
confidence: 99%
“…Consequently, SMN deficiency may impair targeting and local translation of axonal mRNAs essential for motor neuron development and maintenance 44, 45. Furthermore, SMN regulates several other fundamental cellular processes in the neuronal cytoplasm that are critical for maintaining axonal and synaptic health, including endocytic pathways, local translation, mitochondrial transport, and targeting to axons and ubiquitin homeostasis 46, 47, 48, 49, 50, 51…”
Section: How Low Levels Of Smn Cause Smamentioning
confidence: 99%
“…However, an emerging idea is that the loss of additional function(s) of SMN unrelated to RNA splicing could co-contribute to SMA pathogenesis. In particular, it has been strongly suggested that SMN is involved in the trafficking and/or translation of target transcripts (Rossoll et al, 2003;Tadesse et al, 2008;Glinka et al, 2010;Peter et al, 2011;Hubers et al, 2011;Fallini et al, 2011Fallini et al, , 2014Yamazaki et al, 2012;Rathod et al, 2012;Sanchez et al, 2013). In this context, it is noteworthy to mention cross-species conserved genes able to mitigate the SMN loss-of-function defects (Dimitriadi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SMN is needed for stress granule formation (13,14), is found in RNP granules moving through neuronal processes, and is part of RNP complexes implicated in synaptic local translation (15)(16)(17)(18)(19)(20). Additional roles for SMN, in transcription (21), in the PTEN-mediated protein synthesis pathway (22), in translational control (23), and in cell proliferation/differentiation (24), have been described. Importantly, no consensus has been reached regarding the cellular and molecular pathways whose perturbation results in SMA pathology.…”
mentioning
confidence: 99%